The Main Risk Factors Related with Anemia among Preschool Children in Nasiriyah City: Faktor Risiko Utama yang Berhubungan dengan Anemia pada Anak Usia Prasekolah di Kota Nasiriyah - Saadon, Hanan B. (Indonesian Journal on Health Science and Medicine, 2025)
Anemia is a common problem of public health which associated with an increased risk of morbidity and mortality especially in children of poor countries. This study aimed to determine the prevalence and factors that related with anemia in children at pre-school going age. The current study includes 90 children (48 male and 42 female). According to age, 60% of children were under 3 years old, the rest (40%) of children were between 3-6 years old. For male children aged 1-3 years, the hemoglobin level was 6.77 g/dL and 31.25% of them had severe hemoglobin deficiency. As for females in the same age group, the hemoglobin level was 7.40 g/dL, but most of them ( 59.52% ) suffered from moderate anemia. Iron deficiency was found in 14.58 % of male and 23.81% of female, however thalassemia was diagnosed in 18.75 % and 14.29 % of male and female, respectively with non-significant difference (P=0.50). In addition, 41.67% of the male children and 19.05% of the female children were malnourished. Diarrhea was common in both males and females where 39.59 % of males and 54.76% of females presented symptoms of diarrhea. In conclusion, the anemia in children under six years is complex, and highly associated with nutritional status, disease processes, and socio-economic status. If these causes are tackled through better nutrition, access to health and quality education anemia prevalence amongst this group might be greatly reduced. Highlights: High Prevalence in Young Children – Anemia is common among preschool children, with those under three years old being the most affected. Nutritional Deficiencies & Health Conditions – Iron deficiency, thalassemia, malnutrition, and diarrhea contribute significantly to anemia in both male and female children. Need for Comprehensive Interventions – Addressing anemia requires improving nutrition, healthcare access, and socio-economic conditions to reduce its prevalence. Keywords: Anemia in Children, Iron Deficiency Anemia, Malnutrition, Chronic Infections